A description of the diversity of kinship and marriage practices in South Asia with a focus on India. (The South Asianist Journal, 2014)
Whilst not an exhaustive examination, this paper will explore some of the key areas of the diversity of kinship and marriage practices within India. To do so it will look firstly at the formal kinship rules of two well documented communities which are, broadly speaking, representative of practices within their extended regions. From there it will look at the different social functions each of these systems can be argued to serve. From there it will investigate how demographic changes across India are fostering new models of marriage and challenging the formal rules of traditional kinship systems. Next it will look at how the introduction of civil marriage rights is responsible, albeit to a limited extent, for the emergence of yet another model of marriage.  Finally, it will observe that, despite these key differences, there exist some characteristics which remain in place across India.